Espacamento em feijao-de-corda (Vigna siensis Endl.) no Ceará - Braga Paiva, José; Albuquerque, Jackson L. de (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
An experiment was conducted to study the effect of bill spacing on the yield of cow pea (Vigna sinensis Endl.) at Capistrano, Ceará (Brazil) in 1968.